2017
DOI: 10.1080/02770903.2017.1337789
|View full text |Cite
|
Sign up to set email alerts
|

Indirect comparison of bronchial thermoplasty versus omalizumab for uncontrolled severe asthma

Abstract: The ITC should be interpreted cautiously considering the differences between patient populations in the included trials. However, based on the analysis, BT compares well with a potentially more costly pharmacotherapy for asthma. Clinicians evaluating the relative merits of using these treatments should consider the totality of evidence and patient preferences to make an informed decision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Another study, using data from the AIR2 trial of bronchial thermoplasty and two placebo-controlled trials of omalizumab (INNOVATE [67] and EXTRA [68]), reported broadly similar clinical outcomes with the two treatments, including severe exacerbations, emergency department visits, and hospital admissions [66]. Asthmarelated emergency department visits were less for the post-treatment period of the AIR2 trial compared to omalizumab and severe exacerbations were less for omalizumab compared to the total duration of the AIR2 study that included the increase in exacerbations during the pertreatment period [66]. Future studies should assess the cost effectiveness of bronchial thermoplasty with the long-term use of biologics or maintenance oral corticosteroids.…”
Section: Place Of Bronchial Thermoplasty In the Management Of Severe mentioning
confidence: 99%
See 2 more Smart Citations
“…Another study, using data from the AIR2 trial of bronchial thermoplasty and two placebo-controlled trials of omalizumab (INNOVATE [67] and EXTRA [68]), reported broadly similar clinical outcomes with the two treatments, including severe exacerbations, emergency department visits, and hospital admissions [66]. Asthmarelated emergency department visits were less for the post-treatment period of the AIR2 trial compared to omalizumab and severe exacerbations were less for omalizumab compared to the total duration of the AIR2 study that included the increase in exacerbations during the pertreatment period [66]. Future studies should assess the cost effectiveness of bronchial thermoplasty with the long-term use of biologics or maintenance oral corticosteroids.…”
Section: Place Of Bronchial Thermoplasty In the Management Of Severe mentioning
confidence: 99%
“…Other factors that influence the cost-effectiveness of bronchial thermoplasty are a patient's risk of a future exacerbation, the duration of follow-up after treatment and the health systems threshold in dollars for the willingness-to-pay per quality-adjusted life years (QALY). An indirect comparison of bronchial thermoplasty with omalizumab suggested that there was more than a 60% chance that bronchial thermoplasty became cost-effective relative to omalizumab and standard therapy at the willingness-to-pay of $100,000 per QALY in patients with moderate-to-severe allergic asthma in the United States [64,66]. Another study, using data from the AIR2 trial of bronchial thermoplasty and two placebo-controlled trials of omalizumab (INNOVATE [67] and EXTRA [68]), reported broadly similar clinical outcomes with the two treatments, including severe exacerbations, emergency department visits, and hospital admissions [66].…”
Section: Place Of Bronchial Thermoplasty In the Management Of Severe mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 28 ] An indirect comparison of the BT posttreatment period to ongoing treatment with Omalizumab showed no significant differences in the risk for severe exacerbations. [ 29 ] In recent years, two new anti-interleukin 5 (anti-IL-5) mAb medicines have been approved for the eosinophilic phenotype of asthma. Numerous other targeted therapies for asthma are on the horizon.…”
Section: What Are the New Pharmacological Options For Severe Asthma?mentioning
confidence: 99%
“…In recent years, considerable debate has arisen over how to best phenotype and treat patients with severe asthma. While biological therapies are increasingly used to treat such patients, bronchial thermoplasty is an effective [1], nonpharmacological treatment option for a subset of severe asthmatic subjects whose symptoms are not controlled [2].…”
Section: Introductionmentioning
confidence: 99%